Co-registration of Sequential Multidetector Computed Tomography Studies for the Evaluation of Surgical Instrumentation following Resection of Spinal Tumors - J. Matthew Debnam; T. Linda Chi; Leena Ketonen; Yasser M. M. Mahfouz; Nandita Guha-Thakurta (Case Reports in Radiology)
Surgical resection of spinal tumors involves complex reconstructive procedures. The stability and integrity of the surgical construct are evaluated with multidetector computed tomography (MDCT). As coregistration, or fusion, of different imaging modalities, especially positron emission tomography/computed tomography (PET/CT), is common practice, we sought to determine if this technique could be applied to sequential, postoperative MDCT studies of the spine. Herein, we demonstrate that by utilizing the Hermes workstation, co-registration of MDCT spine studies can be performed. This technique allows sequential MDCT examinations of the post-operative spine to be viewed together as one study and may aid in evaluation of the position and integrity of the surgical construct over time. Further study and refinement of this technique will be necessary before clinical implementation.